2020
DOI: 10.1039/c9mh01498e
|View full text |Cite
|
Sign up to set email alerts
|

Giant spin Seebeck effect through an interface organic semiconductor

Abstract: Interfacing an organic semiconductor C 60 with a non-magnetic metallic thin film (Cu or Pt) has created a novel heterostructure that is ferromagnetic at ambient temperature, while its interface with a magnetic metal (Fe or Co) can tune the anisotropic magnetic surface property of the material. Here, we demonstrate that sandwiching C 60 in between a magnetic insulator (Y 3 Fe 5 O 12 : YIG) and a non-magnetic, strong spin-orbit metal (Pt) promotes highly efficient spin current transport via the thermally driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 39 publications
5
26
0
1
Order By: Relevance
“…On the other hand, inserting an intermediate material with a higher work function (corresponding to negative v) suppresses the spin conductance. Our result is consistent with experimental results that enhancement between 300% to 600% were achieved when intermediate materials such as Ru [18], monolayer WSe 2 [21], multilayer MoS 2 [23,24], and C 60 [22] are inserted at the Pt-YIG interface [47]. The enhancement has previously been attributed to the reduction of conductivity mismatch at the Pt/YIG interface, i.e., the spin mixing conductance g Pt/YIG is smaller than the total conductance of Pt/X/YIG trilayer [48].…”
Section: B One-layer Strategysupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, inserting an intermediate material with a higher work function (corresponding to negative v) suppresses the spin conductance. Our result is consistent with experimental results that enhancement between 300% to 600% were achieved when intermediate materials such as Ru [18], monolayer WSe 2 [21], multilayer MoS 2 [23,24], and C 60 [22] are inserted at the Pt-YIG interface [47]. The enhancement has previously been attributed to the reduction of conductivity mismatch at the Pt/YIG interface, i.e., the spin mixing conductance g Pt/YIG is smaller than the total conductance of Pt/X/YIG trilayer [48].…”
Section: B One-layer Strategysupporting
confidence: 92%
“…Another strategy is to reduce the conductivity mismatch at the interface by inserting another layer of material [17], which is proven to be very successful. Large enhancement of SSE through NM/FI interface was demonstrated experimentally by inserting atomically thin magnetic and non-magnetic metals, semiconductors, as well as layers of antiferromagnetic insulator (AFI) [19][20][21][22][23][24][25][26]. While reduction of interfacial conductivity mismatch is a general strategy, a new possibility in optimizing effective magnon-electron coupling on top of the static electron-magnon coupling exists.…”
Section: Introductionmentioning
confidence: 99%
“…We also note that the value of 1800 s is much lower than other low temperature SSE measurements where Peltiers are used to heat the sample. 20 in the HFS signal as a function of applied magnetic field for different heat flux, where the value at μ 0 H = 0 has been subtracted from each dataset to make it easier to observe the field variation. This is shown for 150 K, as the increase in Johnson noise made it difficult to observe at higher temperatures.…”
Section: B Example Measurementsmentioning
confidence: 99%
“…It has been reported that when C 60 is deposited on a substrate the structural distortion transition may exhibit enhancement of SOC 19,29 . There are very few reports on generation of pure spin current in FM/OSC system 17,[30][31][32][33] . Inserting a small C 60 layer can reduce the conductivity mismatch between YIG and Pt 31,33 .…”
mentioning
confidence: 99%
“…There are very few reports on generation of pure spin current in FM/OSC system 17,[30][31][32][33] . Inserting a small C 60 layer can reduce the conductivity mismatch between YIG and Pt 31,33 . The presence of C 60 also decrease perpendicular magnetic anisotropy (PMA) of YIG and enhance spin a) Electronic mail: sbedanta@niser.ac.in mixing conductance across YIG/C 60 /Pt interfaces 33 .…”
mentioning
confidence: 99%